2015
DOI: 10.1016/j.tiv.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Deconjugation of soy isoflavone glucuronides needed for estrogenic activity

Abstract: Soy isoflavones (SIF) are present in the systemic circulation as conjugated forms of which the estrogenic potency is not yet clear. The present study provides evidence that the major SIF glucuronide metabolites in blood, genistein-7-O-glucuronide (GG) and daidzein-7-O-glucuronide (DG), only become estrogenic after deconjugation. The estrogenic potencies of genistein (Ge), daidzein (Da), GG and DG were determined using stably transfected U2OS-ERα, U2OS-ERβ reporter gene cells and proliferation was tested in T47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…In our study, the observed differences could be explained by the higher proportion of free isoflavones (aglycones) in rodents than in humans (Setchell et al, 2011) as it is hypothesized that aglycone forms are more bioactive than conjugated forms (M. A. Islam et al, 2015).…”
Section: Discussionmentioning
confidence: 66%
“…In our study, the observed differences could be explained by the higher proportion of free isoflavones (aglycones) in rodents than in humans (Setchell et al, 2011) as it is hypothesized that aglycone forms are more bioactive than conjugated forms (M. A. Islam et al, 2015).…”
Section: Discussionmentioning
confidence: 66%
“…As red Maca aqueous extract also contains other organic compounds such as polyphenols, tanins, saponins, alkaloids, steroids or glycosides with oestrogenic and androgenic activity (Dini, Tenore, & Dini, 2002; Piacente, Carbone, Plaza, Zampelli, & Pizza, F I G U R E 1 Red Maca aqueous extract did not affect viability of LNCaP cells. Another possibility is that glucosinolates could need to be metabolised for activating anticancer properties in the prostate cancer cells (Islam et al, 2015). At 24 or 48 hr after treatment, cultured cells were processed to measure their viability as described in the Material and Methods section.…”
Section: Discussionmentioning
confidence: 99%
“…The genistein conjugates tested so far, including genistein‐7‐O‐glucuronide (G‐7G), genistein‐7‐O‐sulfate (G‐7S) and genistein‐4′‐O‐sulfate (G‐4′S), appeared inactive in assays for oestrogenicity, leading to the conclusion that the action of the soy phytoestrogen genistein will be mainly related to the plasma and tissue concentration of the free aglycone (Yuan et al, ; Islam et al, ).…”
Section: Introductionmentioning
confidence: 99%